Internalization of Anti-Corruption Values at the University of Lampung: Integrative Curriculum - Junaidah Junaidah; Syarifah Nurbaiti; Riduan Riduan; Amilda Amilda (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe the integrated anti-corruption values in Islamic Religious Education courses at the University of Lampung. The research method used is qualitative with a phenemological approach. Data obtained through observation, interviews, and documentation, data analysis steps using condensation, data presentation and conclusion drawing. The results of this study indicate that the internalization of anti-corruption values uses an integrative model. The nine anti-corruption values are integrated into four materials, namely God and religion, human nature and the universe, the sources of Islamic teachings; and creed, sharia, morality and muamalah. Internalization of these values uses the method of Small Group Discussion, Role-Play and Simulation, Discovery Learning, Self-Directed Learning, Cooperative Learning, Collaborative Learning, Contextual Teaching and Learning, Project Based Learning.